Impact of PD-L1 expression, driver mutations and clinical characteristics on survival after anti-PD-1/PD-L1 immunotherapy versus chemotherapy in non-small-cell lung cancer: A meta-analysis of randomized trials. (2nd December 2018) - Huang, Qingyuan; Zhang, Hua; Hai, Josephine; Socinski, Mark A.; Lim, Eric; Chen, Haiquan; Stebbing, Justin
ABSTRACT: Purpose : To investigate the impact of programmed death-ligand 1 (PD-L1) expression, oncogenic mutations, and clinical characteristics on survival after treatment with anti-PD-1/PD-L1 antibodies versus chemotherapy in non-small cell lung cancer (NSCLC). Patients and Methods : This meta-analysis included randomized trials comparing anti-PD-1/PD-L1 antibodies with chemotherapy. Hazard ratios (HRs) and 95% confidence interval (CI) for overall survival (OS) for the trial population and prespecified subgroups were extracted. We calculated pooled estimates of treatment efficacy using the fixed-effects or random-effects model when appropriate. All statistical tests were two sided. Results : Seven trials involving 3871 patients were included. The pooled results showed that anti-PD-1/PD-L1 immunotherapy significantly prolonged OS (HR: 0.73; 95% CI, 0.63 to 0.84) and PFS (HR: 0.84; 95% CI, 0.71 to 0.99) compared to chemotherapy. OS benefit from immunotherapy were observed in all PD-L1 expression subgroups (negative: HR, 0.79; 95% CI, 0.67 to 0.93; weak-positive: HR, 0.80; 95% CI, 0.67 to 0.95; strong-positive: HR, 0.61; 95% CI, 0.47 to 0.78). Strong-positive PD-L1 expression showed a trend towards more benefit compared to weak-positive PD-L1 expression (interaction P = 0.08). KRAS mutant (HR: 0.60; 95% CI, 0.39 to 0.93), EGFR wild-type (HR: 0.73; 95% CI, 0.61 to 0.87) and smoker (HR: 0.70; 95% CI, 0.60 to 0.83) subgroups achieved significant OS benefit from immunotherapy compared to corresponding subgroups. Survival benefit to immunotherapy was not significantly associated with histology, CNS metastases, age, gender and performance status. Conclusion : This study confirmed that treatment with anti-PD-1/PD-L1 improves overall survival compared with chemotherapy. Benefit was seen, regardless of PD-L1 expression levels; however, PD-L1 strong-positive patients trended to have greatest benefit. Patients with a KRAS mutant or EGFR wild-type tumor have improved survival benefit from immunotherapy compared with KRAS wild-type or EGFR mutant NSCLC, respectively.